2002
DOI: 10.1126/science.1068788
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Saccadic Suppression

Abstract: In normal vision our gaze leaps from detail to detail, resulting in rapid image motion across the retina. Yet we are unaware of such motion, a phenomenon known as saccadic suppression. We recorded neural activity in the middle temporal and middle superior temporal cortical areas during saccades and identical image motion under passive viewing conditions. Some neurons were selectively silenced during saccadic image motion, but responded well to identical external image motion. In addition, a subpopulation of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
197
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(223 citation statements)
references
References 25 publications
20
197
3
1
Order By: Relevance
“…Strong local motion responses would thus be elicited in that feature map, but at many locations in the visual field, so that the entire feature map would become inhibited by the long-range competition mechanism because not containing any single location that significantly differs from most other locations. A consequence of this for human vision is that, at least in our model, an explicit mechanism for top-down saccadic suppression may be unnecessary (Thiele, Henning, Kubischik, & Hoffmann, 2002), although this remains to be tested (i.e., maybe even better agreement between model and humans could be obtained after addition of explicit saccadic suppression to the model). Additional difficulties which would tend to make the simulation with the third model variant more difficult include smearing of the low-pass filtered saliency map as the input shifted (which we often observed when inspecting the dynamic saliency maps predicted for various video clips), competition between possibly salient objects outside the video screen area and objects within that area, and lack of sufficient persistence to allow for salience to build up over time (remember that the saliency map is modelled as leaky integrator neurons, which respond better when inputs are somewhat stable).…”
Section: Discussionmentioning
confidence: 96%
“…Strong local motion responses would thus be elicited in that feature map, but at many locations in the visual field, so that the entire feature map would become inhibited by the long-range competition mechanism because not containing any single location that significantly differs from most other locations. A consequence of this for human vision is that, at least in our model, an explicit mechanism for top-down saccadic suppression may be unnecessary (Thiele, Henning, Kubischik, & Hoffmann, 2002), although this remains to be tested (i.e., maybe even better agreement between model and humans could be obtained after addition of explicit saccadic suppression to the model). Additional difficulties which would tend to make the simulation with the third model variant more difficult include smearing of the low-pass filtered saliency map as the input shifted (which we often observed when inspecting the dynamic saliency maps predicted for various video clips), competition between possibly salient objects outside the video screen area and objects within that area, and lack of sufficient persistence to allow for salience to build up over time (remember that the saliency map is modelled as leaky integrator neurons, which respond better when inputs are somewhat stable).…”
Section: Discussionmentioning
confidence: 96%
“…This would seem to exclude high-level visual areas such as the dorsal medial superior temporal area (MSTd), where retinotopy is crude (Saito et al, 1986), and V1, where saccade-related activity is minimal (Wurtz and Mohler, 1976). Cortical areas such as V3, V4, and the middle temporal area (MT) thus appear to be reasonable candidates, as all three have an approximately logarithmic map of visual space (Albright and Desimone, 1987;Gattass et al, 1988;Motter, 2009) and receive extraretinal signals related to saccadic eye movements (Nakamura and Colby, 2000;Tolias et al, 2001;Thiele et al, 2002;Ibbotson et al, 2007). Indeed, Krekelberg et al (2003) have reported that the population output of MT appears to exhibit a neuronal correlate of perceptual compression.…”
Section: Neurophysiological Implicationsmentioning
confidence: 99%
“…Such suppressive effects are typically not noticeable because they are very brief, existing about 50 ms before the eye movement, extending throughout the eye movement, and terminating about 50 ms following the eye movement (Diamond, Ross, & Morrone, 2000). Saccadic suppression may be mediated at peripheral levels of visual processing (Roska, Nemeth, Orzo, & Werblin, 2000;Thilo, Santoro, Walsh, & Blakemore, 2004) as well as at cortical levels (Thiele, Henning, Kubischik, & Hoffmann, 2002) and affect both parvocellular and magnocellular pathways (Anand & Bridgeman, 2002;Burr, Morrone, & Ross, 2002). Saccadic suppression also may involve a distortion of visual space (Cho & Lee, 2003) and involve an extraretinal component (Diamond et al, 2000).…”
Section: Head Movement Suppressionmentioning
confidence: 99%